Ultrasound-guided ankle block: An attractive anaesthetic technique for foot surgery - Girón-Arango, Laura; Vásquez-Sadder, María Isabel; González-Obregón, María Patricia; Gamero-Fajardo, Carlos Enrique (Colombian Journal of Anesthesiology, 2015)
Foot innervation, defined as distal to the tibial and fibular malleoli, is provided by five nerves, namely the tibial, peroneal (deep and superficial), sural and saphenous nerves. Blockade of these nerves is referred to as ankle block. The main advantage of using this block in foot surgery over other regional techniques is the absence of motor blockade above the ankle, which allows faster mobility after surgery. The use of ultrasound for this block has been shown to be of higher clinical efficacy when compared to a landmark approach. The purpose of this continuing education article is not only to detail the anatomy and sonoanatomy of the five nerves innervating the foot, but the ultrasound technique as well. The ultrasound-guided ankle block can be used alone as anaesthetic technique or as adjuvant for analgesia in foot surgery.